Cardiorenal AL amyloidosis: risk stratification and outcomes based upon cardiac and renal biomarkers. (24th May 2019) - Rezk, Tamer; Lachmann, Helen J.; Fontana, Marianna; Naharro, Ana Martinez; Sachchithanantham, Sajitha; Mahmood, Shameem; Petrie, Aviva; Whelan, Carol J.; Pinney, Jennifer H.; Foard, Darren; Lane, Thirusha; Youngstein, Taryn; et al.
Summary: Systemic AL amyloidosis is a cause of type 5 cardiorenal syndrome. Response to treatment is currently reported according to organ‐specific amyloidosis consensus criteria (ACC), which are not validated in cardiorenal AL amyloidosis. Of 1000 patients prospectively enrolled into the UK ALchemy study, 318 (32%) had combined cardiac and renal amyloidotic organ dysfunction at diagnosis, among whom 199 (63%) died; median survival by Kaplan–Meier analysis was 18·5 months. Fifty (16%) patients required renal replacement therapy (RRT). At diagnosis, independent predictors of death and dialysis were N‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP) >8500 ng/l (hazard ratio [HR] 3·30, P  < 0·001; HR 3·00, P  < 0·001), and estimated glomerular filtration rate (eGFR) < 30 ml/min/1·73 m 2 (HR 1·89, P  = 0·011; HR 6·37, P  < 0·001). At 6 months, an increase in NT‐proBNP of >30% and a reduction in eGFR of ≥25% were independent predictors of death (HR 2·17, P  = 0·009) and dialysis (HR 3·07, P  = 0·002), respectively. At 12 months, an increase in NT‐proBNP >30% was highly predictive of death (HR 3·67, P  < 0·001) and dialysis (HR 2·85, P  = 0·010), whereas ACC renal response was predictive of neither. Cardiorenal AL amyloidosis is associated with high early mortality. Outcomes are dictated by NT‐proBNP and eGFR at diagnosis rather than proteinuria, and thereafter predominantly by changes in NT‐proBNP concentration.